Rerouting of NADPH synthetic pathways for increased protopanaxadiol production in Saccharomyces cerevisiae. Issue 1 (December 2018) - Kim, Jae-Eung; Jang, In-Seung; Sung, Bong; Kim, Sun; Lee, Ju
Abstract Ginseng (Panax ginseng ) and its bioactive components, ginsenosides, are popular medicinal herbal products, exhibiting various pharmacological effects. Despite their advocated use for medication, the long cultivation periods of ginseng roots and their low ginsenoside content prevent mass production of this compound. YeastSaccharomyces cerevisiae was engineered for production of protopanaxadiol (PPD), a type of aglycone characterizing ginsenoside. PPD-producing yeast cell factory was further engineered by obtaining a balance between enzyme expressions and altering cofactor availability. Different combinations of promoters (P GPD, P CCW12, andP ADH2 ) were utilized to construct the PPD biosynthetic pathway. Rerouting the redox metabolism to improve NADPH availability in the engineeredS .cerevisiae also increased PPD production. Combining these approaches resulted in more than an 11-fold increase in PPD titer over the initially constructed strain. The series of metabolic engineering strategies of this study provides a feasible approach for the microbial production of PPD and development of microbial platforms producing other industrially-relevant terpenoids.